HELMINTHOFAUNA OF THE GASTROINTESTINAL TRACT OF ANIMALS FROM THE FELIS CATI DOMESTICUS FAMILY OF THE URALSK CITY - Abirova, I.M (Science and education. - 2021, 2021)
The relevance of the problem of intestinal helminth infections of domestic carnivores is due to the widespread infestation in animals and humans. Helminths of domestic carnivores, cats in particular, have long been the subject of special interest as pathogens of human and domestic productive animals. With such a large number of cats, in addition, many of them are neglected, the problem of environmental pollution by feces of these animals in urban areas is becoming increasingly acute. The cat has been living next to humans for about 6,000 years. Currently, there are domestic, stray, feral and true feral cats. Stray cats find shelter in attics and basements of houses, feed themselves and their numbers are constantly increasing. Some stray animals head for the woods, especially in rural areas, become feral and embittered. Domestic cats, on the other hand, become the most tense factors of contamination of infestation elements in the home, yards and public places. Актуальность проблемы борьбы с кишечными гельминтозами домашних плотоядных обуславливается широким распространением инвазии у животных и человека. Гельминты домашних плотоядных в частности кошек, издавна являются объектом особого интереса - как возбудители болезней человека и домашних продуктивных животных. При такой большой численности кошек, к тому же многие из них безнадзорны, проблема загрязнения окружающей среды фекалиями этих животных в городских условиях становится все более острой. Кошка живет рядом с человеком уже около 6 тыс. лет. В настоящее время существуют домашние, бродячие, одичалые и настоящие дикие кошки. Бродячие кошки находят приют на чердаках и в подвалах домов, питаются самостоятельно и их число постоянно растет. Часть бездомных животных направляются в леса, особенно в сельской местности, дичают и становятся озлобленными. Домашние же кошки становятся наиболее напряженными факторами контаминации инвазионных элементов в доме, дворах и общественных местах.
Keywords: отечественное издание; научный журнал; периодическое издание; гельминтозы; инвазии у животных; гельминтозы у кошек